Potensi Suplementasi Nira Aren (Arenga pinnata Merr.)Terhadap Performa Ayam Broiler - Luky Wahyu Sipahutar; Khairani Khairani (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The research aims was to know the effect supplementation of nira aren in driking water on performance broiler. A total of 100 DOC of CP strain were used, the observation was conducted for 32 day. Designs were a completely randomized design with five observation and four replications (5 birds each). The treatments consisted of P1(control diet), P2 (control diet + 5% supplementation of nira aren on driking water), P3 (control diet + 10% supplementation of nira aren on driking water), P4 (control diet + 15% supplementation of nira aren on driking water), P5 (control diet + 20% supplementation of nira aren on driking water). The variabel observation was performance (feed consumption, body weight, feed conversion ratio). The result showed that supplementation of nira aren on driking water produced significantly (P<0,05) increased body weight and decreased feed conversion ratio compared to those without nira aren supplementation. The concluded that supplementation of nira aren on drinking water increases performance of broiler.Keyword: Broiler, Nira aren, Performance